On Religious Liberty and Secularism in Plural Societies - Fong, Edmund (Asia journal of theology, 2024)
This article argues that a rightly framed understanding of religious liberty and secularism in a plural society facilitates public square deliberation. Addressing first the religious (Christian) constituent, I demonstrate how the Noahic covenant and the traditional doctrines of eschatology, anthropology, and missiology push toward promoting religious liberty for all. By implication, a full-bodied religious liberty welcomes different voices in public square deliberations. Conversely, in addressing the nonreligious constituent, I explore how one dimension of the urge to exclude religious voices from public square deliberations comes from a misguided understanding that the secularization of a society is automatically accompanied by the emptying out of religion and religious beliefs. Rather, a more appropriate secularism focuses on the neutrality of the public square and does not prohibit religious voices in public square deliberations. I conclude by highlighting a philosophy of pluralism that captures this rightly framed understanding of religious liberty and secularism—covenantal pluralism.